2008
DOI: 10.2337/db07-0520
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Glucose-Stimulated Insulin Secretion Is Coupled With Exocrine Pancreatic Lesions in the Cohen Diabetic Rat

Abstract: The association of the in vivo insulin secretory defect with lipid accumulation and activated macrophage infiltration in the exocrine pancreas suggests that changes in the islet microenvironment are the culprit in the insulin secretory malfunction observed in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
69
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 53 publications
7
69
0
Order By: Relevance
“…We have observed previously that the development of hyperglycemia in CDs rats fed HSD is associated with peri-islet infiltration of fat and macrophages ex-pressing IL-1␤ (49). We also showed that copper supplementation to HSD improves GSIS, suggesting the involvement of COX (48).…”
supporting
confidence: 55%
See 1 more Smart Citation
“…We have observed previously that the development of hyperglycemia in CDs rats fed HSD is associated with peri-islet infiltration of fat and macrophages ex-pressing IL-1␤ (49). We also showed that copper supplementation to HSD improves GSIS, suggesting the involvement of COX (48).…”
supporting
confidence: 55%
“…The Cohen diabetic rat is a genetic model of nutritionally induced diabetes (49,50) consisting of two contrasting strains, the diabetes-sensitive rat (CDs) that develops hyperglycemia due to impaired GSIS when fed a high-sucrose, low-copper diet (HSD) but maintains normoglycemia on a regular diet and the diabetes-resistant rat (CDr), which maintains normoglycemia on HSD (49). We have observed previously that the development of hyperglycemia in CDs rats fed HSD is associated with peri-islet infiltration of fat and macrophages ex-pressing IL-1␤ (49).…”
mentioning
confidence: 99%
“…This islet inflammation could be mediated by CCL2 and CCL13 produced in human beta cells. Islet inflammation was also present in animal models for type 2 diabetes, namely the high-fat-diet-fed and db/db mice [18,36], the Cohen diabetic rat [36] and the Goto-Kakizaki rat [37,38]. The role of these infiltrating macrophages is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The role of these infiltrating macrophages is unknown. Some propose them to be beneficial to islet function by promoting angiogenesis [39]; others suggest that activated CD68 + cells could cause beta cell dysfunction and death [36,37]. The beta cell inflammatory response was presently reproduced at the RNA and protein level in ND human islets by their in vitro exposure to the saturated NEFA palmitate, and was dependent on the canonical mediator of early inflammation IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…4). A similar discrepancy between in vivo and in vitro islet function was observed in other animal models of diabetes displaying islet inflammation (46,47).…”
Section: Discussionmentioning
confidence: 77%